Modified Asphalt Using Buton Natural Rock Asphalt - Satrio, Eko Muliawan (Universitas Islam Sultan Agung, 2024)
he characteristics of asphalt mostly determine how well asphalt pavements work. High temperatures can cause stress on the asphalt surface layer. At high temperatures, irreversible alteration or bubbling occurs and leads to spalling as it travels. This is due to the slow movement of the asphalt components in the pavement mixture, which resists the strain caused by traffic. This is because the pavement mix's viscous asphalt matrix flow resists stresses brought on by vehicles. As a result, the rheological characteristics of asphalt, which may be altered, have a significant impact on pavement performance. In this study, Pen. 60/70 asphalt was modified by using Buton Natural Rock Asphalt (BNRA). A total of 10 to 25% of fine BNRA passing sieve #200 was added to the asphalt. Four mixtures of asphalt and BNRA were then tested for penetration and softening point. From the Penetration and Softening Point test results, thePenetration Index (PI) was determined. The PI results obtained were 0; 0.2; 0.1; 0.1; and 0.4 for BNRA content of 0, 10, 15, 20, and 25%. The higher the PI value of asphalt, the lower its temperature susceptibility. It can be seen that with the addition of BNRA, the asphalt is more resistant to temperature changes. While it is evident that BNRA affects the resistance of asphalt to temperature changes, it is also evident that its strength.